DELAYED DEATH IN LONG SCARF SYNDROME - AN UNUSUAL PRESENTATION: A CASE REPORT - Kumari, Mamta; Chawla, Hitesh; Dixit, Praveen; Sandeep, Dara (Journal of Forensic Medicine and Toxicology, 2024)
Background: Death by strangulation is most commonly homicidal in manner. Accidental strangulation is rare. In only a handful of the documented cases, the survival rate has been notably low. This can be attributed to several factors. Hypoxia can lead to organ damage and failure if not promptly addressed. Additionally, injuries to vital structures such as the carotid arteries, can have catastrophic consequences, including severe bleeding or stroke. Fractures in the neck area can also pose significant risks, as they may damage the spinal cord or cause other critical injuries. Taken together, these factors contribute to the lethal nature of this condition, emphasizing the importance of swift medical intervention and specialized care to improve outcomes. Case Report: A 15-year-old female was brought for a medicolegal autopsy at a tertiary care institute in southern Haryana with a history of road traffic accident. As per the history, the deceased was wearing a long
Keywords: Strangulation; Accident; Pneumothorax; Pneumomediastinum